Evolution of the obscura group Drosophila species.: III. phylogenetic relationships in the subobscura cluster based on homologies of chromosome A - Brehm, A. (2020)
The Drosophila subobscura cluster comprises D. subobscura, D. madeirensis and D. guanche, species closely related to some interspecific crosses are possible. This paper clarifies definitively the homologies of the segments of the sex chromosome A (= X) among these species and thus permits a phylogenetic seriation of them. This seriation is identical to the one suggested by the study of chromosome O and concordant with similar data for the remaining three rod autosomes (J, U and E), which, however, do not provide qualitative evidence on this subject.